2011
DOI: 10.5194/angeo-29-1049-2011
|View full text |Cite
|
Sign up to set email alerts
|

Cluster observations of trapped ions interacting with magnetosheath mirror modes

Abstract: Abstract. Mirror modes are among the most intense low frequency plasma wave phenomena observed in the magnetosheaths of magnetized planets. They appear as large amplitude non-propagating fluctuations in the magnetic field magnitude and plasma density. These structures are widely accepted to represent a non-linear stage of the mirror instability, dominant in plasmas with large ion beta and a significant ion temperature anisotropy T ⊥ /T > 1. It has long been recognized that the mirror instability both in the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
53
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 43 publications
7
53
0
Order By: Relevance
“…Kis et al, 2007) and in the magnetosheath (e.g. Souček and Escoubet, 2011). We will show that the ion foreshock includes the kinetic features present in Omidi et al (2005), while mirror mode structures in the magnetosheath display characteristics present in Southwood and Kivelson (1993), Souček et al (2008), promising fruitful avenues for further global simulations.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Kis et al, 2007) and in the magnetosheath (e.g. Souček and Escoubet, 2011). We will show that the ion foreshock includes the kinetic features present in Omidi et al (2005), while mirror mode structures in the magnetosheath display characteristics present in Southwood and Kivelson (1993), Souček et al (2008), promising fruitful avenues for further global simulations.…”
Section: Introductionmentioning
confidence: 80%
“…In the magnetosheath region the simulations presented here as well as in Pokhotelov et al (2013) reproduce highly anisotropic biMaxwellian distributions and associated mirror mode structures. Such anisotropic distributions and large scale mirror mode structures are routinely observed deep in the magnetosheath (Souček and Escoubet, 2011;Souček et al, 2008). Other instabilities that are responsible for the generation of smaller scale ion cyclotron waves observed in the magnetosheath are not resolved in the current simulations due to insufficient spatial resolution.…”
Section: Conclusion and Summarymentioning
confidence: 86%
“…Such mirror mode structures with spatial scales of a few ion inertial lengths are routinely observed across the Earth's magnetosheath (Soucek et al, 2008). The loss cone seen in the magnetosheath ion distribution is also a characteristic feature of the mirror modes and is due to ion trapping between magnetic mirrors (Soucek and Escoubet, 2011).…”
Section: Global Magnetospheric Simulationmentioning
confidence: 86%
“…The electrons could affect the threshold of mirror instability and also the scale size of magnetic holes, but not very significantly. Recent observations have also shown that the trapped ions could be heated at intermediate pitch angles and cooled at small parallel velocities in the trough of nonlinear mirror mode structures (Soucek and Escoubet, 2011).…”
Section: Introductionmentioning
confidence: 99%